PERAN HUKUM KEBIJAKAN PUBLIK DALAM PENCEGAHAN POLITIK DINASTI DI DAERAH - Akhmad Faishal; Mustofa Kamil; Bachtiar Kemal Harahap; Muslimin; Teddy T Pingak; Rifqi Syifa’ul Qolbi (Berajah Journal, 2026)
Dynastic politics is a phenomenon rooted in Indonesia's democratic system, particularly at the regional government level. The practice of dynastic politics threatens the principles of meritocracy, equality, and substantive democracy that form the constitutional foundation of this country. This article aims to analyze the role of public policy law in preventing dynastic politics practices in regions. The research method used is qualitative with a normative-empirical legal approach. Data was collected through document studies, literature studies, and analysis of legislation. The results show that public policy law has a strategic role in preventing dynastic politics through three main mechanisms: first, normative regulation through legislation that limits dynastic politics practices; second, supervision and law enforcement mechanisms by state institutions; and third, political education and formation of community legal awareness. This article recommends the need for harmonization of legislation, strengthening of supervisory institutions, and revitalization of political education to create a regional democratic system free from dynastic politics practices.